EFEKTIVITAS UNIT LAYANAN ADMINISTRASI DALAM PENGELOLAAN DATA DI SEKRETARIAT DAERAH PROVINSI SULAWESI UTARA - PANE, TEGAR; TULUSAN, FEMMY; TAMPI, GUSTAAF BUDDY (Sam Ratulangi University, 2020)
This study aims to determine whether the administrative service unit has been effective in managing datain the Regional Secretariat of North Sulawesi Province. This type of research used in this study is qualityresearch. The theory used is based on four characteristics of the effectiveness of public services, namely:timeliness of service, accuracy of service, courtesy and friendliness, ease of getting service. Source of dataused in this study are primary data and secondary data. Data collection techniques used are three, namely:interviews, observation, and documentation, data obtained from various sources are then analyzed to be aconclusion of the research process. The results of this study that the management of data in theadministrative service unit based on the timeliness of services in the administrative service unit startingfrom the data management process to the approval of existing data or correspondence, service accuracy orminimize errors in services or transactions during the data management process is located in theadministrative service unit, then entering into courtesy and friendliness in managing data in theadministrative service unit, the ease of getting services in data management is easily and quickly resolved.But there are some things that must be considered, namely employees and leaders must attend training orincrease human resources in managing system-based data, adding supporting facilities for datamanagement processes, improving network quality and administrative service unit applications so that thedata management process is completed according to the target even faster than the target that has been set.Keywords: Effectiveness, Administrative Services, Data Management